Youth Unemployment and Innovative Employment Creation (IEC) among University Undergraduates in Nigeria - Akanle, Olayinka; Ademuson, Adefolake O; Morakinyo, Precious A (Journal of Urban Sociology, 2025)
Youth unemployment has become a pervasive issue globally, with profound implications for individuals, communities and economies, particularly in Nigeria where a substantial portion of the youth is absorbed into informal sectors characterized by low productivity, minimal job security and limited access to social benefits. This study examined the innovative employment creation in the midst of widespread unemployment among youths in Ibadan specifically investigating the reasons youth engage in Innovative Employment Creation (IEC), the challenges faced and the coping mechanisms adopted. IECs are new and usual economic activities and business efforts youths engage in to earn income so as to escape unemployment which is widespread and a social reality in Nigeria. Descriptive research design was used. Human Capital Theory was used as theoretical framework. Structured questionnaire and in-depth interviews (IDIs) were used to gather data. Findings suggest that addressing the challenges of youth unemployment and promoting entrepreneurship requires a collaborative approach involving educational institutions, government agencies, private sectors and community stakeholders. It is therefore recommended that all the above-mentioned stakeholders should enhance access to entrepreneurship education and training programs while supports to youths are key as they continue to innovate to combat widespread youths unemployment in Nigeria and Africa.Keywords: youth, unemployment, innovative employment creation, undergraduate students